Proteomic Analysis of Pig (Sus scrofa) Olfactory Soluble Proteome Reveals O-Linked-N-Acetylglucosaminylation of Secreted Odorant-Binding Proteins - Nagnan-Le Meillour, Patricia; Vercoutter-Edouart, Anne-Sophie; Hilliou, Frédérique; Le Danvic, Chrystelle; Lévy, Frédéric (Frontiers in Endocrinology, 2014)
The diversity of olfactory binding proteins (OBPs) is a key point to understand their role in molecular olfaction. Since only few different sequences were characterized in each mammalian species, they have been considered as passive carriers of odors and pheromones. We have explored the soluble proteome of pig nasal mucus, taking benefit of the powerful tools of proteomics. Combining two-dimensional electrophoresis, mass spectrometry and western-blot with specific antibodies, our analyses revealed for the first time that the pig nasal mucus is mainly composed of secreted OBP isoforms, some of them being potentially modified by O-GlcNAcylation. An ortholog gene of the glycosyltransferase responsible of the O-GlcNAc linking on extracellular proteins in Drosophila and Mouse (EOGT) was amplified from tissues of pigs of different ages and sex. The sequence was used in a phylogenetic analysis, which evidenced conservation of EOGT in insect and mammalian models studied in molecular olfaction. Extracellular O-GlcNAcylation of secreted OBPs could finely modulate their binding specificities to odors and pheromones. This constitutes a new mechanism for extracellular signaling by OBPs, suggesting that they act as the first step of odor discrimination.